The aryl hydrocarbon receptor controls cyclin O to promote epithelial multiciliogenesis - Matteo Villa (Nature Portfolio, 2016)
Epithelia are barriers against environmental insults and express the transcription factor aryl hydrocarbon receptor (AhR). Here the authors show that AhR regulates multiciliogenesis via cyclin O and Multicilin in a Notch-dependent manner and that this is blocked by toxic ligands.